Solution-mediated nanometric growth of α-Fe2O3 with electrocatalytic activity for water oxidation. Issue 9 (23rd July 2020) - Taniguchi, Asako; Kubota, Yuta; Matsushita, Nobuhiro; Ishii, Kento; Uchikoshi, Tetsuo
Abstract : This paper describes a simple, low-temperature, and environmentally friendly aqueous route for the layer-by-layer nanometric growth of crystalline α-Fe2 O3 . Abstract : This paper describes a simple, low-temperature, and environmentally friendly aqueous route for the layer-by-layer nanometric growth of crystalline α-Fe2 O3 . The formation mechanism involves alternative sequences of the electrostatic adsorption of Fe 2+ ions on the surface and the subsequent onsite oxidation to Fe 3+ . A combination analysis of X-ray diffraction, scanning electron microscopy, UV-Vis spectroscopy, and X-ray photoelectron spectroscopy revealed that α-Fe2 O3 is directly formed without post-growth annealing via designed chemical reactions with a growth rate of ca. 1.7 nm per deposition cycle. The obtained α-Fe2 O3 layer exhibits electrocatalytic activity for water oxidation and, at the same time, insignificant photo-electrocatalytic response, indicating its defective nature. The electrocatalytic activity was tailored by annealing up to 500 °C in air, where thermal diffusion of Sn 4+ into the α-Fe2 O3 lattice from the substrate probably provides an increased electrical conductivity. The subsequent surface-modification with Ni(OH)2 lowers the overpotential (250 mV at 0.5 mA cm −2 ) in a 1 M KOH solution. These findings open direct growth pathways to functional metal oxide nanolayers via liquid phase atomic layer deposition.